Moisture retention characteristics of soils under Hevea in India - Krishnakumar A K; Datta B; Potty S N (Indian Journal of Natural Rubber Research, 1990)
A study on the moisture retention characteristics of soils under Hevea in India had been carried out. The soils belong to the orders Alfisol and Ultisol. Profiles representing the major rubber growing regions in the traditional rubber growing tract in the South Western coast of India were collected and analysed for the moisture retentive capacity. The moisture retentive capacity of the soils had been found to vary. The moisture retention at -0.033 MPa renged from 19.50 per cent in the profile from Calicut to 37.80 per cent in the profile from Goa, in the surface layers. Nevertheless, the available water storage capacity (AWSC) did not show much variation as a result of the uncomitant increase in the moisture retained at -1.5 MPa. The moisture retention at the above two tension ranges were found to be influenced by clay, sesquioxides, silt and organic matter, in consortium. The moisture retained at -1.5 MPa was more than 0.4 times clay, suggesting that clay is either not well dispersed or some water is held by gels. Silt has been found to play an active role in conjunction with clay in the moisture retention at -1.5 MPa suggesting colloidally active nature of silt in tropical soils. The study on the moisture retention points that the soils in general have high retention potential and this is of high practical significance in a rainfed crop like rubber. The data reveal that 36 per cent of the available moisture is desorbed at -0.1 MPa and 75 per cnet at -0.5 MPa indicating that the tension ranges could be of relevance to the water availability to Hevea.
Keywords: Alfisol; Available water storage capacity; Hevea brasiliensis; Moisture tension range; Soil analysis; Ultisol